Private universities in the shaping of entrepreneurial youth subjectivities (Revista Peruana de Investigación Educativa, 2016)
This article is an ethnographic account of my experience as an enrolled student in one of the most popular private universities in Perú. I take special interest in describing the courses of personal education that occupy an important part of the curriculum in this institution. Based on Foucault’s theory of governmentality, I aim to analyze critically the content of these courses, the way they relate with the emergence of entrepreneurial subjects and its implications for citizenship formation.
Keywords: private university; entrepreneurship; citizenship; ethnography; subject; governmentality